Homer's The Odyssey - Robinson, Margaret A. (Woodbury, N.Y. : Barron's, 1984)
A guide to reading "The Odyssey" with a critical and appreciative mind encouraging analysis of plot, style, form, and structure. Also includes background on the author's life and times, sample tests, term paper suggestions, and a reading list.
Bibliography: p. 84.
Keywords: Homer; Homer; Odysseus (Greek mythology) in literature; Epic poetry, Greek -- Examinations -- Study guides